Inventory and Analysis of Maritime Lexicons in an Ecolinguistic Perspective within the Mandar Community of Gili Tapan (e-Journal of Linguistics, 2026)
This research aims to inventory, classify, and analyze in-depth the maritime lexicon of the Mandar ethnic community residing on Gili Tapan Island, West Nusa Tenggara. The study employs an ecolinguistic perspective to understand the interconnectedness between linguistic systems, marine ecosystems, and the sociocultural dynamics of the speech community. A descriptive qualitative approach was utilized, incorporating the simak-libat-cakap (engaging observation) technique, participant observation, and in-depth interviews. The results indicate that the Mandar community of Gili Tapan possesses a rich maritime lexicon structured into various semantic categories, such as boat nomenclature, fishing gear, traditional navigation, and marine natural phenomena. From an ecolinguistic standpoint, these lexicons reflect the interdependence between humans and the marine environment. However, the modernization of fishing gear, shifting economic patterns, and marine ecosystem degradation have triggered a shift in local lexicon usage. This trend potentially leads to language loss regarding traditional Mandar maritime knowledge